# |
ODE |
Mathematica |
Maple |
\[
{}y^{\prime \prime }+8 y^{\prime }+7 y = 165 \,{\mathrm e}^{4 t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-8 y^{\prime }+17 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-6 y^{\prime }+9 y = {\mathrm e}^{3 t} t^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+6 y^{\prime }+13 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+8 y^{\prime }+17 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = {\mathrm e}^{t} \sin \left (t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 y^{\prime }+40 y = 122 \,{\mathrm e}^{-3 t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-9 y = 24 \,{\mathrm e}^{-3 t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 y^{\prime }+13 y = {\mathrm e}^{2 t} \sin \left (3 t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y = 1
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y = t
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y = {\mathrm e}^{3 t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y = \sin \left (2 t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y = \sin \left (t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-6 y^{\prime }+9 y = 1
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-6 y^{\prime }+9 y = t
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-6 y^{\prime }+9 y = {\mathrm e}^{3 t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-6 y^{\prime }+9 y = {\mathrm e}^{-3 t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-6 y^{\prime }+9 y = {\mathrm e}^{t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \operatorname {Heaviside}\left (t -3\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \operatorname {Heaviside}\left (t -3\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = \operatorname {Heaviside}\left (t -2\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = \operatorname {Heaviside}\left (t -2\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+9 y = \operatorname {Heaviside}\left (t -10\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \left \{\begin {array}{cc} 0 & t <1 \\ 1 & 1<t <3 \\ 0 & 3<t \end {array}\right .
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = \left \{\begin {array}{cc} 0 & t <1 \\ 1 & 1<t <3 \\ 0 & 3<t \end {array}\right .
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+9 y = \left \{\begin {array}{cc} 0 & t <1 \\ 1 & 1<t <3 \\ 0 & 3<t \end {array}\right .
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 3 \delta \left (t -2\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \delta \left (t -2\right )-\delta \left (t -4\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = \delta \left (t -3\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = \delta \left (t -1\right )-\delta \left (t -4\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+2 y = 4 \delta \left (t -1\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = \delta \left (t \right )+\delta \left (t -\pi \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = -2 \delta \left (t -\frac {\pi }{2}\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+3 y = \delta \left (t -2\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+3 y^{\prime } = \delta \left (t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+3 y^{\prime } = \delta \left (t -1\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+16 y = \delta \left (t -2\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-16 y = \delta \left (t -10\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = \delta \left (t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y^{\prime }-12 y = \delta \left (t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y^{\prime }-12 y = \delta \left (t -3\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+6 y^{\prime }+9 y = \delta \left (t -4\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-12 y^{\prime }+45 y = \delta \left (t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+9 y^{\prime } = \delta \left (t -1\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-16 y = \delta \left (t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-2 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-2 x y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\frac {2 y}{2 x -1} = 0
\] |
✓ |
✓ |
|
\[
{}\left (x -3\right ) y^{\prime }-2 y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime }-2 x y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\frac {y}{x -1} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\frac {y}{x -1} = 0
\] |
✓ |
✓ |
|
\[
{}\left (1-x \right ) y^{\prime }-2 y = 0
\] |
✓ |
✓ |
|
\[
{}\left (-x^{3}+2\right ) y^{\prime }-3 x^{2} y = 0
\] |
✓ |
✓ |
|
\[
{}\left (-x^{3}+2\right ) y^{\prime }+3 x^{2} y = 0
\] |
✓ |
✓ |
|
\[
{}\left (1+x \right ) y^{\prime }-x y = 0
\] |
✓ |
✓ |
|
\[
{}\left (1+x \right ) y^{\prime }+\left (1-x \right ) y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime \prime }-2 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+x y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+4\right ) y^{\prime \prime }+2 x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-3 x^{2} y = 0
\] |
✓ |
✓ |
|
\[
{}\left (-x^{2}+4\right ) y^{\prime \prime }-5 x y^{\prime }-3 y = 0
\] |
✓ |
✓ |
|
\[
{}\left (-x^{2}+1\right ) y^{\prime \prime }-x y^{\prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 x y^{\prime }+6 y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}-6 x \right ) y^{\prime \prime }+4 \left (x -3\right ) y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+\left (x +2\right ) y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}-2 x +2\right ) y^{\prime \prime }+\left (1-x \right ) y^{\prime }-3 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime }-x y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-x y^{\prime }-2 x y = 0
\] |
✓ |
✓ |
|
\[
{}\left (-x^{2}+1\right ) y^{\prime \prime }-x y^{\prime }+\lambda y = 0
\] |
✓ |
✓ |
|
\[
{}\left (-x^{2}+1\right ) y^{\prime \prime }-2 x y^{\prime }+\lambda y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-x^{2} y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y \,{\mathrm e}^{2 x} = 0
\] |
✓ |
✓ |
|
\[
{}\sin \left (x \right ) y^{\prime \prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+x y = \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-\sin \left (x \right ) y^{\prime }-x y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\cos \left (y\right ) = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-y \,{\mathrm e}^{x} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-\tan \left (x \right ) y = 0
\] |
✓ |
✓ |
|
\[
{}\sin \left (x \right ) y^{\prime \prime }+x^{2} y^{\prime }-y \,{\mathrm e}^{x} = 0
\] |
✓ |
✓ |
|
\[
{}\sinh \left (x \right ) y^{\prime \prime }+x^{2} y^{\prime }-y \,{\mathrm e}^{x} = 0
\] |
✓ |
✓ |
|
\[
{}\sinh \left (x \right ) y^{\prime \prime }+x^{2} y^{\prime }-y \sin \left (x \right ) = 0
\] |
✓ |
✓ |
|
\[
{}{\mathrm e}^{3 x} y^{\prime \prime }+\sin \left (x \right ) y^{\prime }+\frac {2 y}{x^{2}+4} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+\frac {\left (1+{\mathrm e}^{x}\right ) y}{1-{\mathrm e}^{x}} = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}-4\right ) y^{\prime \prime }+\left (x^{2}+x -6\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime \prime }+\left (1-{\mathrm e}^{x}\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}\sin \left (\pi \,x^{2}\right ) y^{\prime \prime }+x^{2} y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-y \,{\mathrm e}^{x} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y \,{\mathrm e}^{2 x} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y \cos \left (x \right ) = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y \ln \left (x \right ) = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y \,{\mathrm e}^{x} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+3 x y^{\prime }-y \,{\mathrm e}^{x} = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime \prime }-3 x y^{\prime }+y \sin \left (x \right ) = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y \ln \left (x \right ) = 0
\] |
✓ |
✓ |
|
\[
{}\sqrt {x}\, y^{\prime \prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+\left (6 x^{2}+2 x +1\right ) y^{\prime }+\left (2+12 x \right ) y = 0
\] |
✓ |
✓ |
|